Fractional Generating Function from The Square Root of Two with A-B Goen Numbers - Stephanus Ivan Goenawan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
The square root of two is an irrational number that cannot be written as a fraction of the numerator and denominator. By using the generating function of A-B Goen, from the resulting set of numbers, the sequence of A-B Goen numbers can be obtained by selecting integer numbers. The A Goen numbers are generated from the generator function which have integer numbers, while the B Goen numbers are obtained from the sequence numbers. In this study, through the generating function of A-B Goen, it can be proven that the division between the A Goen number and the B Goen number in an infinite sequence will result the value of the square root of two.